A circRNA-miRNA-mRNA regulatory network associated with the treatment response to tuberculosis. (January 2021) - Tan, Wei; Zhang, Li; Wang, Shanmei; Jiang, Ping
Abstract: Objectives: The high morbidity and mortality of tuberculosis (TB) have severe socio-economic consequences, and there is an urgent need to explore the mechanisms driving TB development and progression. The aim of this study was to analyze the regulatory RNAs and target genes involved in TB, in order to identify key genetic biomarkers for diagnosing and treating TB. Methods: Circular RNAs (circRNAs), microRNAs (miRNAs) and messenger RNA (mRNAs) expression profiles of TB patients and healthy controls were downloaded from the GEO database. A circRNA–miRNA–mRNA competing endogenous RNA (ceRNA) network was constructed using the differentially expressed circRNAs (DEcircRNAs), miRNAs (DEmiRNAs), and mRNAs (DEmRNAs). The DEmRNAs in this network were functionally annotated using GO and KEGG analyses, and ordinal regression analysis was used to identify the genes correlated to the treatment response in TB patients. Results: We identified 133 DEmRNAs, 37 DEcircRNAs and 173 DEmiRNAs between the TB and healthy controls, from which 30 DECircRNAs, 27 DEmiRNAs and 35 DEmRNAs were used to construct the ceRNA network. CACNA1I, IGF2BP3, LPCAT2, SPOCK2 and IRF2 were significantly correlated with the anti-TB therapeutic response (P < 0.05). Conclusion: A TB-associated DEcircRNA-miRNA-mRNA ceRNA network was constructed, of which some DEmRNAs potentially influence the treatment response. Highlights: We identified a TB-related DEcircRNA-miRNA-mRNA ceRNA network through bioinformatics analysis. We identified that CACNA1I, IGF2BP3, LPCAT2, SPOCK2 and IRF2 were significantly correlated with the anti-TB therapeutic response.